In vivo Outcomes of the Application of Stem Cell-derived Conditioned Medium (Secretome) or Its Derivatives toward Skin Flap Following Ischemia–Reperfusion Injury: A Systematic Review of Experimental Studies - Richard Christian Suteja; I. Gusti Ayu Maha Hiranandini Prawista; I. Komang Hotra Adiputra; Giovanca Verentzia Purnama; Darren Junior; I. Gusti Ngurah Ariestha Satya Diksha; I. Gusti Ngurah Dinda Pratyaksa; I. Dewa Gede Agung Siwa Guptha; Novea Indratmo; Albert Salim; I. Putu Divanaya Suryanov; Gede Wara Samsarga (Turkish Journal of Plastic Surgery)
Skin flaps are tissue transferred from a donor to a recipient site to fill covering defects in the surface of the body. During transfer, skin flaps are severely predisposed to ischemia not only due to ischemia but also to ischemia–reperfusion (I/R) injury, a paradoxical exacerbation of cellular death following blood flow restoration in tissues exposed to ischemic insults. This systematic review aimed to report the in vivo outcomes of the application of stem cell-derived conditioned medium (secretome) or its derivatives toward skin flap following I/R injury in experimental studies. This study was a systematic review with literature searched using Science Direct, PubMed, Directory of Open Access Journal, Cochrane Central, Clinicaltrials.gov, and Europe PMC on January 24, 2024, for studies reporting the effects of stem cell-derived conditioned medium (secretome) or its derivatives in the skin flap I/R injury in animal models. We obtained a total of 318 studies during the search, which were then screened. Ten studies were included in the review. Our study found that stem cell-conditioned medium increases overall flap survivability; promotes vascularization, perfusion, and angiogenesis; reduces inflammation, reduces apoptosis and oxidants; and increases collagen secretion and maturation. The effect was found to be even more profound when the stem cells were set to proliferate under hypoxic conditions. Secretome did not only exhibit prosurvival and proproliferation properties suitable for responding to ischemic insults but also anti-inflammatory and antiapoptotic properties suitable for responding to I/R injury. Furthermore, secretome also assisted native structure recovery. The results from the experimental studies found that secretome is a promising therapy to increase flap survivability when also promoting histology recovery.